2016
DOI: 10.3892/mmr.2016.5001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal profiles of blood pressure, circulating nitric oxide, and adrenomedullin as predictors of clinical outcome in acute ischemic stroke patients

Abstract: Stroke remains an important health and social challenge. The present study investigated whether blood pressure (BP) parameters and circulating levels of nitric oxide metabolites (NOx) and adrenomedullin (AM) may predict clinical outcomes of stroke. Patients (n=76) diagnosed with acute ischemic stroke were admitted to the stroke unit and clinical history data and monitored parameters were recorded. Blood plasma was collected at days 1, 2, and 7 to measure NOx and AM levels. Infarct volume, neurological severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 57 publications
2
28
4
Order By: Relevance
“…Nearly all prior studies have shown that higher blood pressure during the acute phase of stroke is associated with worse outcomes . A majority of these studies have demonstrated specifically that higher values of SBP immediately after treatment with intravenous tPA is associated with worse functional outcomes and hemorrhagic complications .…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all prior studies have shown that higher blood pressure during the acute phase of stroke is associated with worse outcomes . A majority of these studies have demonstrated specifically that higher values of SBP immediately after treatment with intravenous tPA is associated with worse functional outcomes and hemorrhagic complications .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we cannot generalize and say that AM is always neuroprotective. For instance, high levels of circulating AM correlate with increased neurological severity in stroke patients (Serrano-Ponz et al, 2016 ) and endothelial AM seems to have the reverse effect on stroke and brain damage than neuronal AM (Ochoa-Callejero et al, 2016 ). Until we acquire a more complete understanding on the effects of AM in the CNS, our present data need to be interpreted on their own, indicating that lower levels of AM are beneficial for memory preservation, especially in females.…”
Section: Discussionmentioning
confidence: 99%
“…hAM has a variety of physiological functions, including vasodilatation, hormone secretion, neurotransmission, embryogenesis, wound healing, and immunoregulation [Kitamura et al, ; Beltowski and Jamroz, ]. hAM has therapeutic effects in experimental models of ischemic heart disease, inflammatory bowel disease (IBD), stroke, and retinochoroidal disease [Nakamura et al, ; Nishikimi et al,; Iesato et al, ; Serrano‐Ponz et al, ].…”
Section: Introductionmentioning
confidence: 99%